Synergy Between the General Election Commission (KPU) and the Election Supervisory Board (BAWASLU) of Palembang City in the Ongoing Data Updating During the COVID-19 Pandemic - Sari, Novta Ria (Ampera: A Research Journal on Politics and Islamic Civilization, 2023)
The institutional relationship between the KPU and Bawaslu can be viewed from the relationship of their respective inseparable mandates and authorities as election organizers. To increase the synergy of the KPU and Bawaslu in Palembang City in the context of inputting continuous updating data during the Covid-19 pandemic, so that if there is a further data election the updated ones are appropriate and this selection will work as expected. Conversely, if communication between these institutions is not well established, it will lead to conflict. The impact of the democratic process in the form of elections will be hampered. Therefore, to establish communication or relations between the KPU and the election supervisory body (Bawaslu) to achieve the expected election success, so that the data that will be updated by the KPU will continue to be updated. Therefore the author is interested in researching with the research title ''The Synergy of KPU and BAWASLU Palembang City in updating sustainable data during the Covid-19 pandemic'' with the formulation of the following problems: 1. How is the synergy of KPU and Bawaslu City of Palembang in sustainable updating in the future? the covid-19 pandemic? 2. What are the obstacles faced by the Palembang City Election Commission in updating sustainable data during the Covid-19 pandemic? Based on the results of research conducted and reinforced by data found in the field on research concerning the problem of the synergy of KPU and BAWASLU in updating sustainable data during the Covid -19 pandemic. The researcher found the results of his research that the general election commission is not only the organizer of the election, but also has the task of managing data on sustainable choices that must always be updated every month for updating election data. For the synergy that exists between the KPU and BAWASLU in terms of updating continuous data during a pandemic, very well established because it really requires coordination between the two related agencies to solve problems faced in terms of updating data during the Covid-19 pandemic which was very limited in movement due to obstacles such as data sources, community participation in updating data and budget funds.